Achieving and Understanding of Highly Efficient Ternary Organic Photovoltaics: From Morphology and Energy Loss to Working Mechanism. Issue 9 (5th August 2022) - Li, Shuixing; Zhan, Lingling; Li, Yaokai; He, Chengliang; Zuo, Lijian; Shi, Minmin; Chen, Hongzheng
Abstract: Ternary strategy, adding an additional donor (D) or acceptor (A) into conventional binary D:A blend, has shown great potential in improving photovoltaic performances of organic photovoltaics (OPVs) for practical applications. Herein, this review is presented on how efficient ternary OPVs are realized from the aspects of morphology, energy loss, and working mechanism. As to morphology, the role of third component on the formation of preferred alloy‐like‐phase and vertical‐phase, which are driven by the miscibility tuning, is discussed. For energy loss, the effect of the third component on the luminescence enhancement and energetic disordering suppression, which lead to favorable increase of voltage, is presented. Regarding working mechanism, dilution effect and relationships between two acceptors or donor/acceptor, which explain the observed device parameters variations, are analyzed. Finally, some future directions concerning ternary OPVs are pointed out. Therefore, this review can provide a comprehensive understanding of working principles and effective routes for high‐efficiency ternary systems, advancing the commercialization of OPVs. Abstract : Ternary blend is a widely used strategy for higher efficiencies in organic photovoltaics. In this review, recent high‐efficiency works applying ternary strategy from three views of morphology, energy loss, and working mechanism are summarized, thus providing a comprehensive understanding on the role of third component.